Longitudinal bending stiffness of cycling footwear - What is stiff enough? - Litzenberger, S.; Tran, D.-M.; Michel, F. I. (Journal of Science and Cycling, 2023)
To investigate the influence of a cycling shoe`s longitudinal bending stiffness on the kinematics of the cyclist`s foot, three identical leisure-cycling shoes for flat pedals with different longitudinal bending stiffness were tested during indoor trials with twelve male subjects riding at five intensities in seated and standing cycling, respectively. Using an infrared-based 3D motion capture system and power output measurement with a crank-based power meter it was shown that power output does not differ significantly between shoes with different sole stiffness, that metatarsophalangeal angle between forefoot and rearfoot is increasing with increasing power and mostly decreasing with increasing bending stiffness of the shoe and that the pedal angle over crank-cycle shows individual differences that can be clustered in three types. Ultimately it can be said that Ethylenvinylacetat (EVA) inlays show excessive bending whereas there is only a small difference between nylon and nylon-carbon inlays.